Juridical Analysis of Home Ownership Credit by Developers to Consumers Not Through Banking (Research Study at PT. Putera Tangkas Baloi Permai) - Andrini, Annisa Rizky; Prasetyasari, Christiani; Fadjriani, Lia; Fadlan, Fadlan (CV. Rayyan Dwi Bharata, 2023)
Home ownership credit (KPR) has 3 (three) parties working together, namely the developer, usually called the developer, the consumer, and of course the bank that finances the home ownership loan. However, currently many developers have the ambition to gain more profits by not involving banks in implementing mortgage activities with consumers. This research discusses the legal regulations for home ownership loans which are regulated in Bank Indonesia Regulation No. 20 of 2018 as well as the application of the KPR Law by developers to consumers who do not go through banking and how to implement, obstacles and solutions related to home ownership credit by developers to consumers who do not go through banking. This research is a type of empirical research that uses primary and secondary data sources and analyzes the data using qualitative analysis to then form sentence descriptions that can be easily understood by readers. Based on the research results, the legal regulations regarding Home Ownership Credit are contained in Bank Indonesia Regulation No. 20 of 2018 which states that there are 3 parties in KPR, namely Developer, Bank, and Customer or Consumer. That the implementation of KPR must be in accordance with applicable regulatory procedures, and it is not permissible to carry out KPR without a bank. That the obstacle that arises if according to the procedure means involving a bank, the obstacle is in the prospective home owner's understanding of the legal provisions and KPR requirements, if without banking the obstacle that arises is the lack of legal certainty for the prospective home owner due to the absence of a bank in implementing KPR activities.